La estrategia CRM, una visión 360º del cliente - Ma. Rosa Llamas Alonso; Jean-Pierre Lévy-Mangin; Ma. Aranzazu Sulé Alonso (Ciencia Ergo Sum)
CRM strategy (customer relationship management) is a business philosophy, stemming from relationship marketing that joins strategy and technology, with the objective of creating value for both customers and the company. In this paper we conceptualise this strategy, stressing key issues as well as challenges faced when implementing a CRM system, from different perspectives: business processes, structure, organizational culture and analytical techniques